A RESPONSABILIDADE DOS AVÓS NA OBRIGAÇÃO ALIMENTAR (REMUNOM, 2024)
This article addresses the possibility of grandparents providing maintenance when the parent is financially insufficient and/or incapable, and cannot partially or fully afford the maintenance obligation. To this end, it will be analyzed the family law and its legal provisions of the Brazilian legal system, as well as the principles of Human Dignity and Family Solidarity, as well as the principles of complementarity and subsidiarity.